Interaction between paliperidone extended release and TS-1®, an oral anticancer drug containing a 5-fluorouracil derivative, in a schizophrenic patient - Yasui-Furukori N (Dove Medical Press, 2013)
Norio Yasui-Furukori, Kojiro Hashimoto, Kazutoshi Kubo, Tetsu Tomita Department of Neuropsychiatry, Graduate School of Medicine, Hirosaki University, Hirosaki, Japan Abstract: Until now there has been no information available on drug interaction between paliperidone and TS-1®, an oral anticancer drug containing a 5-fluorouracil derivative. The patient in the case presented here was a 39-year-old man with a 15-year history of schizophrenia. The patient's usual treatment of 2 mg/day of risperidone was changed to 3 mg/day of paliperidone extended release. He experienced worsening psychotic symptoms after switching from risperidone to paliperidone while he was also receiving TS-1. Retrospective analyses showed plasma concentration of paliperidone was consistently lower during the treatment with TS-1 than without TS-1. This case suggests there is drug interaction between paliperidone extended-release tablets and TS-1. Keywords: schizophrenia, antipsychotic, OROS, diarrhea, Positive and Negative Syndrome Scale